Manajemen Bisnis Syariah Berbasis Kewirausahaan di Pondok Pesantren Mukmin Mandiri Sidoaro - Heri Cahyo Bagus Setiawan; Beni Dwi Komara; Aries Kurniawan (STEI Kanjeng Sepuh Gresik Jawa Timur, 2020)
In the Islamic view, business is not just profit oriented but there are guidelines that underlie it. Islam encourages people to do business activities because it is part of worship or good deeds. Islamic Shari'ah places human relations in their proper place, making humans able to interact with each other in a balanced and mutually beneficial manner. Pesantren (Islamic boarding school) is one of the right places to study Islamic values ​​in business. In this study, researchers observed a managerial at Pesantren (Islamic boarding school) in managing their business activities. To answer the focus of the research question which is about how sharia business management at the Pesantren Mukmin Mandiri (Islamic boarding school), researchers conducted in-depth interviews with Sntri (students) and kiyai (the Leader of Islamic boarding school) totaling 4 people. The result is that, sharia business management practices based on entrepreneurship at the Pesantren Mukmin Mandiri are: 1) Producing Business Products Pesantren Must Be Halal; 2) Al-Quran and Hadith as Basis for Business Management; 3) No False Promises and Overpromise in Business; 4) Intention and Business Covenant in Pesantren (Islamic Boarding Schools) Must Hold Islamic Sharia Principles.